2015
DOI: 10.1007/s11046-015-9949-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota–Gut–Brain Axis: Yeast Species Isolated from Stool Samples of Children with Suspected or Diagnosed Autism Spectrum Disorders and In Vitro Susceptibility Against Nystatin and Fluconazole

Abstract: Autism spectrum disorder (ASD) is a general term for a group of complex neurodevelopmental disorders of brain development that limits a person's ability to function normally. Etiology has not been clearly defined up to date. However, gut microbiota and the bidirectional communication between the gastrointestinal tract and brain, the so-called microbiota-gut-brain axis, are hypothesized, which may be involved in the etiology of several mental disorders. Recent reports suggest that Candida, particularly Candida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 32 publications
2
59
0
1
Order By: Relevance
“…krusei and Candida . glabrata were not found in healthy children (De Angelis et al, 2013; Kantarcioglu et al, 2016). Strati et al, found a significant increase in the Firmicutes / Bacteroidetes ratio in autistic subjects relative to normal subjects.…”
Section: Relationship Between Asd and Gut Microbiotamentioning
confidence: 99%
“…krusei and Candida . glabrata were not found in healthy children (De Angelis et al, 2013; Kantarcioglu et al, 2016). Strati et al, found a significant increase in the Firmicutes / Bacteroidetes ratio in autistic subjects relative to normal subjects.…”
Section: Relationship Between Asd and Gut Microbiotamentioning
confidence: 99%
“…On the other hand, Candida albicans was the most frequently identified Candida species in the work of Iovene et al (2017). In fact, some studies have pointed out that a high abundance of Candida albicans can cause less carbohydrate and mineral absorption and generate higher toxin levels that could contribute to ASD behaviours (Kantarcioglu et al, 2016). Other authors hypothesized that some Lactobacillus species can modulate the immunological responses to Candida in the GI tract by providing tryptophan-derived aryl hydrocarbon receptor ligands that stimulate the immune system, principally IL-C3 cells, to produce IL-22.…”
Section: Higher or Lower Abundance Of Gut Microbes In Asdmentioning
confidence: 99%
“…At present, the microbiota-gut-brain axis is an explanatory model that attempts to relate, among others, ASD symptoms with findings in neuroscience and bacteriology. The microbiota-gut-brain axis is defined as a bi-directional communication system between the neuronal, immune, endocrine and metabolic pathways, but it still requires better understanding (Sudo et al, 2004;Hiippala et al, 2016;Kantarcioglu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, her symptoms were not alleviated until the patient had a cesarean section, so we tend to believe that the pneumonia was an additional manifestation of agranulocytosis. [19] Second, due to the relatively long disease duration, the patient may have taken some drugs inducing agranulocytosis, but she could not remember, namely, the existence of information risk of bias. [20] …”
Section: Discussionmentioning
confidence: 99%